Απομόνωση νέου στελέγχους Ochrobactrum SP. D2 με δυνατότητα βιοδιάσπασης φαινανθρενίου - Κωνσταντίνου, Ραφαέλα (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
This thesis focuses on phenanthrene, an organic substance that belongs to the category of polycyclic aromatic hydrocarbons (PAH’s) and is characterized as a major environmental pollutant. Tackling the pollution caused by phenanthrene and other similar substances is proposed to be achieved by using physical methods, such as biodegradation by microbial populations. The purpose of this paper is the isolation of a microorganism from an environmental sample that is polluted with petroleum and finding the optimum cell growth through changes applied in pH, salinity, temperature, and nutrient salts. Furthermore, the process of phenanthrene’s biodegradation was investigated and the maximum quantity that can be departed by the microorganisms in a given period of time was determined as part of this thesis. In order to achieve the isolation of the microorganism, a procedure was followed that is based on various microbiological processes followed by the identification of the strain, by extracting the DNA sample. In the quantitative determination of conditions that favor the development of cell biomass, it was necessary to use spectrophotometrical methods and take measurements in liquid crops for four continuous days. Using the HPLC to study the decay time, results showed a variation in the concentration of phenanthrene by the isolated microorganism over time. Additionally, it became feasible to compare the remaining quantity of phenanthrene with the measurements were taken every time. The results obtained after the completion of the experimental part of this thesis have shown that the isolated microorganism from environment that performed machining operations, polluted with engine oil and grease cars, is a strain of the genus Ochrobactrum, with greater growth in pH 8.5, salinity 10 g/L NaCl and temperature 30 °C. This specific microorganism also showed satisfactory development and in an environment with a lack of nitrogen source. Regarding biodegradation, it was observed that the removal of phenanthrene from the microorganism at a rate of 61.9% over 144 hours, with initial concentration of phenanthrene in 150 mg/L.
Keywords: Phenanthrene; Biodegradation; Ochrobactrum; Φαινανθρένιο; Βιοαποδόμηση